2018
DOI: 10.1097/md.0000000000013437
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin for the treatment of acute variceal bleeding

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 41 publications
2
20
0
3
Order By: Relevance
“…Another meta-analysis that included three studies (n = 302 patients) that compared the efficacy of SSAs with Terlipressin found no statistically significant differences in the control of acute bleeding, the incidence of early recurrence and adverse events, transfusion requirements, or survival [166]. Some meta-analysis found that octreotide provided better bleeding control than vasopressin/terlipressin [167] and terlipressin [168] in patients with acute esophageal variceal bleeding.…”
Section: Acute Bleeding From the Gastrointestinal Tractmentioning
confidence: 99%
“…Another meta-analysis that included three studies (n = 302 patients) that compared the efficacy of SSAs with Terlipressin found no statistically significant differences in the control of acute bleeding, the incidence of early recurrence and adverse events, transfusion requirements, or survival [166]. Some meta-analysis found that octreotide provided better bleeding control than vasopressin/terlipressin [167] and terlipressin [168] in patients with acute esophageal variceal bleeding.…”
Section: Acute Bleeding From the Gastrointestinal Tractmentioning
confidence: 99%
“…A recent meta-analysis reported no difference in rebleeding and mortality with either of these drugs. 27 All patients with suspected variceal bleed received carvedilol as secondary prophylaxis. Carvedilol has been shown to decrease mortality and reduce hepatic venous pressure gradient (HVPG) more than other non-selective beta-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous SRs [6,11,[35][36][37] have compared the efficacy of vasoactive agents with placebo, other vasoactive agents, or other non-pharmacological therapy. Few SRs have attempted to directly compare vasoactive agents used in AVB [10,38], and others have compared different therapies for AVB by network meta-analysis [39][40][41].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…There are two main groups of vasoactive agents for the treatment of AVB: vasopressin (V) and its synthetic analog terlipressin (T), and somatostatin (S) and its synthetic analog octreotide (O) [4][5][6][7]. Vasopressin is a potent systemic vasopressor with splanchnic effects, and T has the same properties but with a longer half-life and apparently fewer adverse effects.…”
Section: Introductionmentioning
confidence: 99%